Becker's nevus and ipsilateral acanthosis nigricans - Vijay Zawar; Tarang Goyal; Sneha Kamra (Our Dermatology Online, 2014)
There is paucity in world literature regarding the simultaneous occurrence of Becker's nevus and ipsilateral acanthosis nigricans in the same individual. There is only case reported previously in world literature. We speculate that our case may further strengthen the view of probable, more than a chance, association of these two entities and suggest need for further exploration of the role of androgen receptors in such cases.